Efficiency of the use of various fertilizers for spring barley - R. V. Nazarov; L. Z. Vakhitova; L. Z. Karimova; R. I. Safin (Зерновое хозяйство России, 2018)
Under the conditions of development of soil and air aridity at the beginning of vegetation, the use of liquid fertilizers for seed and non-root treatment allows optimizing mineral nutrition and controlling the processes of formation of spring barley yield. Thus, when the liquid complex fertilizer ‘Megavit’ is added during disinfection of seeds, the density of plant stand and square of leaf surface increase that positively affect on barley productivity. The productivity increase was 0.31 t/ha. The productivity of the crop increased on 0.69 t/ha after irrigation with the liquid fertilizer ‘Azosol’ at the earing stage, and on 0.96 t/ha after seed treatment with ‘Megavit’ and irrigation with ‘Azosol’. The application of the method significantly reduced the spread and development of the main barley disease in Tatarstan, dark brown rust. It has been determined that non-root fertilizing with ‘Agris’ promotes productivity increase and tolerance to diseases. Non-root fertilizing with these medicines increase a number of kernels pre head and their weight. The use of these technology increases protein content in forage barley. The most efficient was the fertilizer ‘Agris Nitrogen’ with 3.0 l/ha. The use of the method produced barley productivity increase on 0.6 t/ha. the development of dark brown rust reduced in 1.6 times. The content of protein was 13.2% with 12.7% of the control.